Inner excellence eaudiobook Train your mind for extraordinary performance and the best possible life. - Murphy, Jim (Academy of Excellence - New York - Rome - Tokyo, 2023)
Want more joy and confidence when you perform? Discover the life guide that has developed world champions, empowered athletes to become world #1, and most importantly, transformed their hearts and minds. This step-by-step training manual from one of the world's top mental skills coaches will teach you how to train your mind like the very best. My #1 tip for success: Read Inner Excellence by Jim Murphy. - Stewart Cink, British Open Champion, 8-time PGA Tour Winner Whether you're an athlete or entrepreneur, single mother or father of five, you'll find exercises, techniques and tools in this book that will improve every area of your life. Your life will take on new meaning as you move beyond the pursuit of happiness to a life of purpose and fulfillment. Jim Murphy's complete program of proven mental techniques is based on the powerful principles of love, wisdom, and courage, that came from over six years of full-time research and writing (after his masters degree in Coaching Science). "I read the first version of Inner Excellence six times. I recommend all my clients read it." – Matt Killen, PGA Tour coach to Justin Thomas, Tiger Woods and many others INNER EXCELLENCE WILL SHOW YOU HOW TO: DEVELOP SELF-MASTERY—and let go of what you can't control OVERCOME ANXIETY—and build powerful mental habits REMOVE MENTAL BLOCKS—and get out of your own way TRAIN YOUR SUBCONSCIOUS MIND—and release limiting beliefs "Inner Excellence changed how I see the world, how I think, and how I play golf." - Vaughn Taylor, three-time PGA Tour winner Jim Murphy is a Performance Coach (mental skills) to the best athletes and leaders in the world.